Model Pengambilan Keputusan Kepala Sekolah di Mts Irsyadud Diniyah Kabupaten Probolinggo Tahun Pelajaran 2018/2019 - Qiptiah, Devi Mariatul (Universitas Muhammadiyah Jember, 2019)
Decision making is the most important thing that school principals have to perform as part of their role as a school manager. Provided that principals are proficient or has mastered various models for appropriate decision making, both organized and unorganized, in accordance with what is needed by current situations and conditions, the decision might then produce maximum results. This study focused on investigating a model of decision making, be it organized and unorganized, performed by a school principal at at MTs Irsyadud Diniyah Bantaran District, Probolinggo Regency. The general objective of this study was to describe the model of both organized and unorganized level performed by a school principal in MTs Irsyadud Diniyah, Bantaran District, Probolinggo Regency. This study employed a descriptive qualitative approach, the research subjects were selected through purposive sampling technique. Techniques for collecting data were done through interviews, observation, and documentation. Data analysis was carried out through inductive reasonings, and the validity of the data was ascertained through source triangulation and technical triangulation. The results of the study show that, first, the model of decision making performed by a school principal at MTs Irsyadud Diniyah used a model of decision-making on the bases of group discussions, voting, etc. Second, the unorganized decision-making model performed by the principal at MTs Irsyadud Diniyah was based on opinion submission and voting as well as a group-based decision-making model.